ANALISIS KUALITAS PELAYANAN TERHADAP PRESTASI KERJA KARYAWAN PADA LAYANAN (KUKM) KOPERASI DAN USAHA KECIL DAN MENENGAH - Achmad Deni Daruri; Mochamad Ramdan Perdana; Siti Ubaidah; Heberlolo Simbolon (Sekolah Tinggi Manajemen IMMI, 2023)
Service quality is a very important thing to be considered by companies in facing a very competitive situation. Maximum work performance because work performance in a company is very important and must always be improved. The purpose of this study was to determine the magnitude of the influence of the Service Quality variable on Employee Work Performance in Cooperative Services (KUKM) and Small and Medium Enterprises.The sampling technique used in this study the author uses the Random Sampling technique (randomly) using the Suharsimi Arikunto formula (2014). Where each member of the population has the same opportunity to be selected as a sample as a whole obtained 169 employees or 25%, from the entire population so the sample is 42 employees.Based on the results of regression analysis that it turns out that the service quality variable can improve employee performance, the equation value is Y = 8.135 + 0.769 X, there is a positive influence on employee performance, it is necessary to prove by testing the hypothesis that the tcount value = 11,694 ttable value at (40) of = 1.682, then Ho is rejected and Ha is accepted which means it has evidence that Service Quality on Employee Work Performance has a very significant influence. Based on the results of the analysis, there is a positive influence of Service Quality on Employee Work Performance obtained a value of 0.880 so it can be concluded that the influence is very strong or the value of the coefficient of determination (KD) is 77.4%. So the level of influence is 77.4% and the remaining 22.6% is influenced by other factors not observed by the author as a whole. Keywords: Service Quality and Employee Performance